2014
DOI: 10.1016/j.biomaterials.2014.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of curcumin loaded nanoparticles in prostate cancer

Abstract: Prostate cancer is the most commonly diagnosed cancer disease in men in the Unites States and its management remains challenge in everyday oncology practice. Thus, advanced therapeutic strategies are required to treat prostate cancer patients. Curcumin (CUR) is a promising anticancer agent for various cancer types. The objective of this study was to evaluate therapeutic potential of novel poly(lactic-co-glycolic acid)- CUR nanoparticles (PLGA-CUR NPs) for prostate cancer treatment. Our results indicate that PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(157 citation statements)
references
References 52 publications
3
154
0
Order By: Relevance
“…Furthermore, PLGA-PEG nanoparticles are able to enhance the anticancer efficiency of CUR in prostate (Yallapu et al, 2014) and colon (Kim et al, 2011) cancer cell both in vitro and in vivo. The enhancement of CUR activity was also reached by encapsulation into GL-based nanogels able to target the deliver the polyphenol to colon cancer due to pH responsivity (Madhusudana Rao et al, 2015).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Furthermore, PLGA-PEG nanoparticles are able to enhance the anticancer efficiency of CUR in prostate (Yallapu et al, 2014) and colon (Kim et al, 2011) cancer cell both in vitro and in vivo. The enhancement of CUR activity was also reached by encapsulation into GL-based nanogels able to target the deliver the polyphenol to colon cancer due to pH responsivity (Madhusudana Rao et al, 2015).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Many literatures have reported that PCL or PLGA could be served as compatible biomaterials to build nanocarrier-based delivery systems [38][39][40]. Herein, PCL was utilized to stabilize hydrophobic core, while mPEG-PLGA was used to improve the solubility of nanoparticles owing to pegylation [41][42][43][44][45] (Fig.…”
Section: Preparation and Characterization Of The Nanoformulationsmentioning
confidence: 99%
“…All glassware was cleaned with aqua regia (3 parts of concentrated HCl and 1 part of concentrated HNO3), rinsed with distilled water, ethanol and acetone, and oven-dried before use. Tetrachloroauric acid trihydrate (HAuCl4.3H2O), L-ascorbic acid (C6H8O6), sodium citrate (C6H5Na3O7.2H2O), sodium hydroxide (NaOH), 4,7,10,13,16,19,22,25,32 …”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…Targeted delivery of therapeutics may help reduce toxicity and increase efficacy. Recently, novel nanomaterials tagged with relevant targeting ligands have been developed to interact with receptors highly expressed in tumour tissues for safe and efficient delivery of therapeutic cargos in the treatment of prostate cancer [4] [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%